STUDI TRANSFORMASI-ADAPTASI RUANG KOTA DI KAWASAN PUSAT BISNIS KARET KUNINGAN, JAKARTA - Darmady, Irene Syona (Universitas Tarumanagara, 2018)
Karet Kuningan area is an area dominated by various business and commercial centers. The development of Karet Kuningan area is large scale with an average building intensity exceeding 100,000 m2, land tenure above 20,000 m2, and trillions of rupiah investment costs. When viewed from the activities of urban space utilization, land utilization in the Karet Kuningan area is a physical transformation of urban space that was born due to external factors (government policy and the private sector - real estate). The dominance of large-scale development in the Karet Kuningan area has in fact led to the dynamics of functional and physical changes in the surrounding residential areas to adapt. One form of adaptation effort that can be observed is the emergence of various